Energy Direction in Ultrasonic Impregnation of Continuous Fiber-Reinforced Thermoplastics - Popp, Julian; Wolf, Michael; Mattner, Tobias; Drummer, Dietmar (Journal of Composites Science, 2021)

Fiber Orientation in continuous fiber reinforced thermoplastics/metal hybrid joining via multi-pin arrays - Popp, Julian; Busch, Matthias; Hausotte, Tino; Drummer, Dietmar (Science and Engineering of Composite Materials, 2023)
Continuous fiber-reinforced thermoplastics (CFRTs) can in combination with high-strength metals offer characteristics that cannot be achieved with mono-material parts. One possible example is the combination of locally high-temperature resistance in the metal component with superior weight-related mechanical properties due to the CFRT component. This approach requires a reliable and durable joining technology, which considers the material-specific properties and allows to exploit the full potential of CFRT/metal hybrid parts. A promising approach in the field of CFRT/metal joining is the use of metallic pins, which can be embedded in the locally heated CFRT component to create a form-fitting joint. In the current state of the art, primarily single-pins are investigated and characterized: especially the distinct fiber orientation in the direct pin pressing process is only described for single-pin joints. Behind this background, the present study aims at creating an understanding of the fiber orientation mechanism for multi-pin arrays. Therefore, in the scope of this study, unidirectional reinforced glass fiber/polypropylene samples are joined via direct pin pressing and infrared heating with different 1D and 2D multi-pins arrays with different pin-diameters, spacing and pin distributions. The resulting joint morphology is consequently analyzed using micro-computer-tomography. Based on the performed investigations, a model for the fiber displacement mechanism is proposed, and the first recommendations for the design of fiber-friendly multi-pin joints with unidirectional reinforcements are given. It showed that especially pin-spacing in fiber orientation in dependency of the pin diameter is critical for a fully reconsolidated joint quality, and it is suggested that a pin-offset in the fiber direction is beneficial for a fiber-friendly joining process.<br
Keywords: hybrid joining; continuous fiber-reinforced thermoplastics; glass fiber; pin; pin joining; direct pressing; fiber orientation

Fiber Orientation Mechanism of Continuous Fiber Reinforced Thermoplastics Hybrid Parts Joined with Metallic Pins - Popp, Julian; Kleffel, Tobias; Römisch, David; Papke, Thomas; Merklein, Marion; Drummer, Dietmar (Applied Composite Materials, 2021)
Continuous Fiber Reinforced Thermoplastic (CFRT) hybrid parts offer interesting possibilities for lightweight application, which can exceed the capabilities of mono material metal or CFRT parts. In this case, the joining technology oftentimes is the limiting factor. This study investigates a joining operation with metal pin structures which are additively manufactured via powder bed fusion featuring different diameters and tip geometries, which are inserted into the locally infrared heated CFRT part. The resulting fiber rearrangement is assessed using transmitted light microscopy, confocal laser scanning microscopy as well as micro-computer-tomography. It could be shown that for all assessed pin variants a similar distinct fiber displacement can be seen and that the pin diameter has a significant effect on the resulting fiber orientation with smaller pin diameters being advantageous because of gentle fiber displacement and reduced undulation. The tip geometry has only minor effect on the fiber orientation. Especially in the X/Y plane no systematic influence of the tip geometry on the fiber displacement could be observed. Based on the gained insights a three-stage model of the fiber orientation processes is proposed.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Continuous fiber reinforced thermoplastics; Fiber orientation; Hybrid part; Joining; Organo sheet; Pin

Fügen thermoplastischer Faserverbunde über Pin-Strukturen mit variablen Prozessrouten - Popp, Julian; Wolf, Michael; Drummer, Dietmar (Werkstoffe in der Fertigung, 2023)
Keywords: Fügetechnik; Pin-Strukturen; Thermoplasten; Thermoplastische Faserverbunde; Variable Prozessrouten

High Speed Forming of Continuous Fiber Reinforced Thermoplastics - Mattner, Tobias; Popp, Julian; Kleffel, Tobias; Gröschel, Christian; Drummer, Dietmar (Applied Composite Materials, 2020)

Influence of geometrical parameters of conic pin structures in thermoplastic composite/steel hybrid joining - Popp, Julian; Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro; Drummer, Dietmar (Materials Research Proceedings, 2023)
Hybrid parts consisting of continuous fiber reinforced thermoplastic (CFRT) and steel components offer promising potential in lightweight construction. In this approach, the joining operation poses the major challenge due to different physical and chemical properties of both materials. This paper studies a joining method in which conical pin structures, protruding from the surface of the metal component, are inserted into the locally heated CFRT component to create a form fitting joint. The aim is to identify and quantify the influence of the parameters pin height and pin head diameter on the mechanical performance in single lab shear and cross head normal experiments. Based on the results it can be shown, that both an increased pin height and head diameter are beneficial under shear load in means of increased maximum load capacity while under normal load only an increased head diameter has clear benefits. Those effects are led back to the geometrical properties and the resulting stress distributions in the joining area.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Composite; Hybrid Manufacturing; Joining

Influence of pin geometry on the joint strength of CFRT-metal hybrid parts with metallic pins - Popp, Julian; Kleffel, Tobias; Drummer, Dietmar (Joining Plastics - Fügen von Kunststoffen, 2021)
Metal – Continuous Fiber Reinforced Thermoplastic (CFRT) hybrid parts offer new possibilities for lightweight application, which often exceed the capabilities of mono material parts. Oftentimes, in this application, the joining technology is the limiting factor. The present study investigates a joining operation with additively manufactured metal pin structures with different diameters and tip geometries, which are pressed into locally infrared heated CFRT parts. The resulting joint strength is assessed for different pin geometries. It could be shown that pins with larger diameters lead to higher absolute joint strengths and that a fl at cylindrical pin shape is advantageousm in means of joint strength in comparison to tapered pins. When dividing the maximum shear strength by the pin foot cross sectional area as a measure of the utilization of a given joining space, pins with smaller diameter are beneficia

Influence of the Textile Reinforcement on the Joint Formation of Pin-Joined Composite/Metal Parts - Popp, Julian; Drummer, Dietmar (Applied Composite Materials, 2024)

In-Situ Computed Tomography - Analysis of a Single-Lap Shear Test with Composite-Metal Pin Joints - Köhler, Daniel; Popp, Julian; Kupfer, Robert; Troschitz, Juliane; Drummer, Dietmar; Gude, Maik (Journal of Physics: Conference Series, 2023)
Lightweight design in the form of intelligent multi-material structures that combine the advantages of high strength steel and continuous fibre reinforced thermoplastics (CFRTs) gain increasing relevance. In this context, the joining operation is a major challenge as it has to be time and cost efficient and the resulting joint has to exhibit a high mechanical durability. One possible approach is the use of cold formed pin structures, which can be inserted into the CFRT to create a form fitting joint under avoidance of fibre damage as it is commonly the case for bolted or riveted joints. The deformation phenomena of pin joints are usually investigated by macrosectioning or (ex-situ) computed tomography. However, due to resetting elastic deformations and cracks that close after unloading an inaccurate state of the inner joint structure is measured. Furthermore, an investigation of different stages with increasing load and progressing failure is very time consuming, because multiple samples have to be tested and investigated. Alternatively, in-situ computed tomography (in-situ CT) can be used to investigate the testing of pin joints. In this paper, a method for in-situ CT analysis of a single-lap shear test with composite-metal pin joints is presented. The pins are plastically extruded to a height of approx. 1.8 mm from the metal sheet (1.5 mm thick) and are pressed into a locally heated glass fibre reinforced thermoplastic (FRT) sheet (approx. 2 mm thick) creating a form fit. Specimens with quasi-unidirectional fibre reinforcement in 0° and 90° direction are tested. With this procedure, the three-dimensional deformation of the joint can be observed and failure phenomena can be identified for each reinforcement direction respectively. Thus, this method can also be used for validating numerical simulations.
CRIS-Team Scopus Importer:2023-09-15

Investigation of different process routes for joining thermoplastic composite/steel joints via the embedding of cold formed metallic pin structures - Popp, Julian; Drummer, Dietmar (Journal of Advanced Joining Processes, 2024)
This study focuses on the integration of continuous fiber-reinforced thermoplastics (CFRT) with metal components through the use of cold-formed pin structures. Comparing six different joining methods with varying heat generation approaches, we investigated their impact on the mechanical properties and joint integrity. Ultrasonic vibration emerged as a highly promising method, offering both rapid joining operations and favorable mechanical characteristics with average failure loads in lap shear tests of up to 249 N. In comparison, vibration welding showed drawbacks, resulting in CFRT damage, potential pin failure, and diminished mechanical performance with maximum average lap shear loads of 216 N. Additionally, traces of zinc residue were identified on the CFRT surface, raising concerns about the corrosion resistance of the metal component. In summary, vibration welding appears unsuitable for pin joining applications. Infrared heating, while showcasing good mechanical performance with lap shear loads of up to 257 N, proved to be a more time-consuming process compared to ultrasonic joining. It also resulted in inferior mechanical strength under shear load in the direction of the fiber orientation (238 N). To assess the mechanical potential of pin joints relatively to established joining methods, we created and tested adhesively joined reference samples. Pin joints demonstrated a significant advantage under shear load, showing approximately double the shear strength (17.8 MPa) compared to adhesively joined samples (8.9 MPa). However, under normal load, pin joints exhibited lower strength, highlighting the need for further optimization to enhance their practical applicability.
CRIS-Team Scopus Importer:2024-12-13
Keywords: Continous fiber reinforced thermoplastic; Glass fiber; Hybrid joining; Pin; Thermoplastic composites

Joining of CFRT/Steel Hybrid Parts via Direct Pressing of Cold Formed Non-Rotational Symmetric Pin Structures - Popp, Julian; Römisch, David; Merklein, Marion; Drummer, Dietmar (Applied Sciences, 2022)
In this study, quasi-unidirectional continuous fiber reinforced thermoplastics (CFRTs) are joined with metal sheets via cold formed cylindrical, elliptical and polygonal pin structures which are directly pressed into the CFRT component after local infrared heating. In comparison to already available studies, the unique novelty is the use of non-rotational symmetric pin structures for the CFRT/metal hybrid joining. Thus, a variation in the fiber orientation in the CFRT component as well as a variation in the non-rotational symmetric pins’ orientation in relation to the sample orientation is conducted. The created samples are consequently mechanically tested via single lap shear experiments in a quasi-static state. Finally, the failure behavior of the single lap shear samples is investigated with the help of microscopic images and detailed photographs. In the single lap shear tests, it could be shown that non-rotational symmetric pin structures lead to an increase in maximum testing forces of up to 74% when compared to cylindrical pins. However, when normalized to the pin foot print related joint strength, only one polygonal pin variation showed increased joint strength in comparison to cylindrical pin structures. The investigation of the failure behavior showed two distinct failure modes. The first failure mode was failure of the CFRT component due to an exceedance of the maximum bearing strength of the pin-hole leading to significant damage in the CFRT component. The second failure mode was pin-deflection due to the applied testing load and a subsequent pin extraction from the CFRT component resulting in significantly less visible damage in the CFRT component. Generally, CFRT failure is more likely with a fiber orientation of 0° in relation to the load direction while pin extraction typically occurs with a fiber orientation of 90°. It is assumed that for future investigations, pin structures with an undercutting shape that creates an interlocking joint could counteract the tendency for pin-extraction and consequently lead to increased maximum joint strengths.
Keywords: joining of CFRT/metal; hybrid technology; mechanical properties; pin geometry; continuous fiber reinforced thermoplastics

Joining of CFRT-steel hybrid parts via hole-forming and subsequent pin caulking - Römisch, David; Popp, Julian; Drummer, Dietmar; Merklein, Marion (Production Engineering, 2021)
In times of increasing global warming, the awareness of the necessity for significant CO2 reduction is growing. Especially in the transport and aerospace sector, lightweight construction has potential to achieve emission reduction goals by reducing the overall vehicle weight. Thereby, adding lightweight fibre-reinforced composites to materials such as steel and aluminium is used to achieve weight savings. Furthermore, continuous-fibre-reinforced thermoplastics (CFRTs) begin to replace more traditional thermoset thermoplastics due to their easier bulk production and uncomplicated storage. Hybrid parts often consist of a CFRT and a higher strength metal component. Here, the joining process poses the main challenge, due to different chemical and physical properties of the components. In the current state of the art, riveted and bolted joints are commonly used, leading to increased weight due to auxiliary elements and requiring precise bolt holes often destroying load-bearing fibres. Joining with cold formed pin structures is an innovative and versatile joining process, which avoids the need for auxiliary elements. These pins are subsequently inserted in warm formed holes in the CFRT component and then caulked to create a form-fitting hybrid joint. To obtain a fundamental understanding of this joining process, hole-forming and pin-caulking, are investigated in this study. First, the hole-forming with IR-radiation is investigated with regard to suitable process parameters and resulting fibre morphology. The formed holes are consequently mechanically characterized. Second, the caulking-process is investigated by iteratively upsetting a pin and subsequently measuring the geometry. Based on these findings two different suitable caulking degrees are defined and samples for mechanical as well as microscopic investigations are manufactured. The created joints are first investigated via micro-sections and reflected light microscopy to identify possible damage in the CFRT component, which can result from the pin caulking process. Second, a mechanical characterisation under shear load as well as pin extraction loads normal to the sample surface is conducted and the normal load tests are compared with the bearing strength of CFRT samples.
CRIS-Team WoS Importer:2021-12-31

Joining of continuous fiber reinforced thermoplastic/steel hybrid parts via undercutting pin structures and infrared heating - Popp, Julian; Drummer, Dietmar (Journal of Advanced Joining Processes, 2022)
Continuous fiber reinforced thermoplastics (CFRT)/steel hybrid parts offer promising properties and possibilities, which can exceed the capabilities of both individual materials. In this case, the joining operation presents the main challenge. This paper studies the direct pin pressing where metallic pins with undercutting geometries, protruding from the metal component, are inserted into a locally infrared heated CFRT component. The aim is to investigate the joining process with a focus on the filling of the undercut features with matrix and fibers to create a primarily form-fitting joint. For good mechanical properties of the joint, it is crucial, that the undercutting features are filled and do not lead to significant deconsolidations. The pin structures are manufactured from 42CrMo4 steel on a cnc-lathe and are joined via welding with HCT600+Zn sheet metal. The CFRT samples are manufactured from polypropylene and approximately 45% vol. unidirectional glass fibers. In the scope of this study, different pin geometries are joined with varying process settings and micro sections of the joints are investigated via reflected light microscopy. It could be shown that the undercuts can be completely filled with matrix and fiber material using the described process route. Based on the optical investigations a suitable setting of joining parameters is defined and lap shear as well as cross head samples are manufactured and experimentally tested. It could be seen that independently from the pin geometry the lap shear strength was primarily limited due to shear failure of the pin structures and it is assumed that the base diameter and pin strength predominantly determine the joint strength. Cross head samples failed due to pin extraction. Here, a significant increase of the joint strength with undercutting features could be shown in comparison to cylindrical reference pins.
Created from Fastlane, Scopus look-up
Keywords: Fiber damage; Glass fiber; Hybrid technology; Joining of CFRT Metal; Mechanical properties

Joining of steel/CFRT-hybrid parts via non-rotational symmetric cold formed pin structures - Popp, Julian; Drummer, Dietmar (Hybrid 2022, 2022)
Hybrid parts, consisting of a steel and continuous fiber reinforced thermoplastic (CFRT) component offer new possibilities such as the combination of good weight related mechanical properties and high temperature resistance that can exceed the potential of single material parts. This study investigates the direct pin pressing process with single cold formed, non-rotational symmetric pins into a quasi-unidirectional CFRT component. In the current state of the art, primarily rotational symmetric cross sections of the pins are investigated although non-rotational symmetric cross sections could offer potential in means of material and load appropriate joining and introduction of forces into the reinforcing fibers: Depending on the failure mode of the joint, the orientation of the non symmetric pin strucuture is expected to influence the joint characteristic. Consequently, in the scope of this study, three different geometries are investigated: As a baseline geometry, a cylindrical pin with a diameter of 1 mm is used, which is utilized to compare the results of the non-rotational symmetric pins. The second geometry is an oval shaped pin with an aspect ratio of 1:2 and length of the short side of 1 mm aiming at a more gently fiber displacement in the quasi unidirectional composite and also increased bending resistance of the pin structure. The third geometry is a polygon, which is based on a triangular shape with rounded corners and sides and an in-circle diameter of 1 mm aiming at an increased, load direction dependent, joint strength. Thereby, the fiber component is a custom-manufactured quasi-unidirectional CFRT glass fiber/polypropylene composite with a fiber volume content of approximately 45 %. In a first step, the joints are characterized via imaging methods in order to create a thorough understanding of the geometries’ influence on fiber displacement mechanisms. Thereby the structures are joined with the CFRT in different orientations in relation to the fiber direction in order to create a thorough understanding about the anisotropic fiber displacement. In a second step, the joints are characterized in quasi-static single lap shear tests in 0° and 90° to the fiber orientation in order to determine the mechanical performance and the results of the different geometry types. Besides the fiber orientation, the orientation of the non-symmetric pin structures is also varied in relation to the load direction resulting in a total of six tested combinations.

Provision of cross-domain knowledge in mechanical joining using ontologies - Zirngibl, Christoph; Kügler, Patricia; Popp, Julian; Bielak, Christian Roman; Bobbert, Mathias; Drummer, Dietmar; Meschut, Gerson; Wartzack, Sandro; Schleich, Benjamin (Production Engineering, 2022)

Review on mechanical joining by plastic deformation - Meschut, Gerson; Merklein, Marion; Brosius, Alexander; Drummer, Dietmar; Fratini, Livan; Füssel, Uwe; Gude, Maik; Homberg, Werner; Martins, Paulo A. F.; Bobbert, Mathias; Lechner, Michael; Kupfer, Robert; et al. (Journal of Advanced Joining Processes, 2022)
Mechanical joining technologies are increasingly used in multi-material lightweight constructions and offer opportunities to create versatile joining processes due to their low heat input, robustness to metallurgical incompatibilities and various process variants. They can be categorised into technologies which require an auxiliary joining element, or do not require an auxiliary joining element. A typical example for a mechanical joining process with auxiliary joining element is self-piercing riveting. A wide range of processes exist which are not requiring an auxiliary joining element. This allows both point-shaped (e.g., by clinching) and line-shaped (e.g., friction stir welding) joints to be produced. In order to achieve versatile processes, challenges exist in particular in the creation of intervention possibilities in the process and the understanding and handling of materials that are difficult to join, such as fibre reinforced plastics (FRP) or high-strength metals. In addition, predictive capability is required, which in particular requires accurate process simulation. Finally, the processes must be measured non-destructively in order to generate control variables in the process or to investigate the cause-effect relationship. This paper covers the state of the art in scientific research concerning mechanical joining and discusses future challenges on the way to versatile mechanical joining processe
Keywords: Mechanical Joining; Joining processes; Pin-Joining; Clinching; Self-piercing riveting; Versatility